The Restoration of the Panel Painting depicting the Adoration of Shepherds with a Saint Bishop - Claudia Cricchio (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper presents the restoration of a panel painting with frame of the second half of the XVI century and now preserved at the Abatellis (i.e. Galleria Regionale della Sicilia di Palazzo Abatellis, Palermo, Italy). A careful historical and artistic study as well as a diagnostic analysis preceded the restoration that aimed to re-establish a good reading of the painting. The essay focuses on the possibility to reintegrate a missing element of the frame with materials used in the 3D printing, in order to restore its function of “spatial connection” between the painting and the expositive environment. The result of the experimentation was the design of two elements, printed using reverse engineering and a 3D printer, after testing three types of filaments.